2014
DOI: 10.1021/ol501024y
|View full text |Cite
|
Sign up to set email alerts
|

Stereospecific Functionalization of Iodoaziridines via Unstabilized Aziridinyllithiums Generated by Iodine–Lithium Exchange

Abstract: Lithium-iodine exchange on alkyl or aryl substituted N-Ts-iodoaziridines afforded unstabilized aziridinyl lithiums, which were subsequently trapped at low temperatures with a range of carbon and heteroatom electrophiles affording cis-substituted aziridines exclusively. When using isocyanates as electrophiles, access to aziridine carboxamides or 1,3,5-trisubstituted hydantoins can be selected by control of reaction temperature.Aziridines are an important class of saturated heterocycles often used as synthetic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 65 publications
0
9
0
1
Order By: Relevance
“…Varying the reaction conditions was also determining for the obtention of hydantoin derivatives, as shown by Boultwood et al 434 On the one hand, when aziridinyllithium species were reacted with isocyanates in the presence of n-Buli at −100°C, Metal-catalyzed syntheses of hydantoins from isocyanates were besides described. The Ni-catalyzed formation of 1,3,5trisubstituted hydantoins from acrylates in the presence of two equivalents of aryl isocyanates was reported.…”
Section: 5-disubstituted Hydantoinsmentioning
confidence: 99%
“…Varying the reaction conditions was also determining for the obtention of hydantoin derivatives, as shown by Boultwood et al 434 On the one hand, when aziridinyllithium species were reacted with isocyanates in the presence of n-Buli at −100°C, Metal-catalyzed syntheses of hydantoins from isocyanates were besides described. The Ni-catalyzed formation of 1,3,5trisubstituted hydantoins from acrylates in the presence of two equivalents of aryl isocyanates was reported.…”
Section: 5-disubstituted Hydantoinsmentioning
confidence: 99%
“…This stereoconvergence implies that the configuration at the iodine-substituted carbon atom is inconsequential. [11] Trapping of syn-4 a with methyl pinacolyl borate led to boronic acid pinacol ester 5 g in 73 % yield (d.r. Under these conditions, quenching of syn-4 a with various electrophiles led to a range of products of type 5 ( Table 1).…”
mentioning
confidence: 99%
“…= 97:3 (entry 6). [11] Trapping of syn-4 a with methyl pinacolyl borate led to boronic acid pinacol ester 5 g in 73 % yield (d.r. = 97:3; entry 7).…”
mentioning
confidence: 99%
“…15 Furthermore, we demonstrated that N-Ts α-iodoaziridines could be used to generate aziridinyllithium species by Li-I exchange (Scheme 1B). 16 The aziridinyllithium was then trapped with electrophiles, affording N-sulfonyl aziridine derivatives in high yields and with complementary regio-and stereochemistry to deprotonation approaches. We next assessed bulky sulfonyl protecting groups, under slightly different reaction conditions; 1.0 equiv imine, 3.4 equiv CH 2 I 2 , 3.0 equiv LiHMDS.…”
mentioning
confidence: 99%